Attracting foreign students: a strategy for the internationalization of higher education - Исалиева, Сауле; Кошербаева, Айгерим; Малахова, Ирина; Танабаева, Анар (Pedagogy and Psychology, 2020)
The article provides an overview of the main concepts of internationalization of higher education and the current state of internationalization of higher education in Kazakhstan. Basic regulations regulating the development of internationalization strategies are presented. The authors analyze the project Strategy for Internationalization of Abai University for 2020-2025, focusing on the integration of foreign students and PPS into the university environment. The strategy highlights the current state of internationalization, priority areas of development and necessary measures for its implementation, such as designing the educational environment of the university for foreign students, recruiting foreign students, organizing online admissions and distance (mixed) studying, development of educational programs in English, creation of a Center for adaptation and support of foreign students, development of ID card of a foreign student(personal student card), organization of exchange practices in the field of education and science, etc.